An analysis of structure: biomass structure relationships for characteristic species of the western Kalahari, Botswana. (20th May 2013) - Meyer, Thoralf; D'Odorico, Paolo; Okin, Greg S.; Shugart, Herman H.; Caylor, Kelly K.; O'Donnell, Frances C.; Bhattachan, Abi; Dintwe, Kebonyethata
Abstract Savannah ecosystems are important carbon stocks on the Earth, and their quantification is crucial for understanding the global impact of climate and land‐use changes in savannahs. The estimation of aboveground/belowground plant biomass requires tested allometric relationships that can be used to determine total plant biomass as a function of easy‐to‐measure morphological indicators. Despite recent advances in savannah ecology, research on allometric relations in savannahs remains confined to a few site‐specific studies where basal area is typically used as the main morphometric parameter with plant biomass. We investigate allometric relations at four sites along a 950‐km transect in the Kalahari across mean rainfall gradient 170 mm yr−1–550 mm yr−1. Using data from 342 harvested trees/shrubs, we relate basal area, height and crown diameter to aboveground biomass. These relationships are strongest in trees and weakest in small shrubs. Strong allometric relationships are also determined for morphologically similar groups of woody vegetation. We show that crown diameter can be used as an alternative to basal area in allometric relationships with plant biomass. This finding may enhance the ability to determine aboveground biomass over large areas using high‐resolution aerial or satellite imagery without requiring ground‐based measurements of basal area.